2017
DOI: 10.1038/s41477-017-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific activities of the major herbicide-resistance gene BAR

Abstract: Bialaphos resistance (BAR) and phosphinothricin acetyltransferase (PAT) genes, which convey resistance to the broad-spectrum herbicide phosphinothricin (also known as glufosinate) via N-acetylation, have been globally used in basic plant research and genetically engineered crops . Although early in vitro enzyme assays showed that recombinant BAR and PAT exhibit substrate preference toward phosphinothricin over the 20 proteinogenic amino acids , indirect effects of BAR-containing transgenes in planta, including… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…It was shown that glufosinate from the practical and economic points of view turned out to be the best for the control of glyphosate-tolerant weeds in citrus orchards [58]. However, the study of the metabolome in several PPT-tolerant transgenic cultures demonstrated increased accumulation of acetylamino adipate and acetyl tryptophan, which indicated non-specific activity of the bar gene [59]. Perhaps, a more detailed study of the PPT effect on control and transgenic plants would make it possible to clarify the mechanisms of its action and to develop new methods of protection.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that glufosinate from the practical and economic points of view turned out to be the best for the control of glyphosate-tolerant weeds in citrus orchards [58]. However, the study of the metabolome in several PPT-tolerant transgenic cultures demonstrated increased accumulation of acetylamino adipate and acetyl tryptophan, which indicated non-specific activity of the bar gene [59]. Perhaps, a more detailed study of the PPT effect on control and transgenic plants would make it possible to clarify the mechanisms of its action and to develop new methods of protection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, by integrating transcriptomics and metabolomics analysis, we revealed that there were only one gene and eight metabolites differentially expressed in MhSnf7 GM maize. According to the report by Christ et al (2017), transgenic BAR indeed converts plant endogenous aminoadipate and tryptophan to their respective N-acetylated products in several plant species. Our metabolomics data (Table S1) identified 172 compounds with known identity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated considerable metabolic consequences of genetic alterations in potato (Shepherd et al ., ) and wheat (Baker et al ., ), however. Moreover, a recent study using metabolomics revealed that even the commonly used bialaphos resistance gene ( BAR ) for transgene selection has effects on amino acid levels in a range of species as a result of enzyme promiscuity (Christ et al ., ). A further study looking at substantial equivalence in tomatoes revealed that the majority of the transgenics exhibited only small changes in metabolomics yet displayed reproducible transformation‐related metabolic signatures.…”
Section: Metabolomicsmentioning
confidence: 97%